Respuesta :
Answer: - 53
Step-by-step explanation:
For a sequence to be arithmetic sequence then there must be a common difference (d). Common difference is given by :
d = [tex]t_{2}[/tex] - [tex]t_{1}[/tex] = [tex]t_{3}[/tex] - [tex]t_{2}[/tex] ...
From the sequence given :
a = -1
d = -3 - (-1 )
d = -3 + 1
d = -2
The formula for nth term of an arithmetic sequence is given as :
[tex]t_{n}[/tex] = a + ( n - 1 ) d
where n is the number of terms , therefore, the 27th term will be
[tex]t_{27}[/tex] = a + (27 - 1 ) d
substituting the value of a and d , we have
[tex]t_{27}[/tex] = - 1 + (26) x -2
[tex]t_{27}[/tex] = -1 -52
[tex]t_{27}[/tex] = -53
Therefore , the 27th term = - 53